Libertarianism in Pop Culture: : Applying libertarian principles to Buffy the Vampire Slayer’s Season 4 - Lins, Marcella (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
Television drama is an important tool to present hypothetical scenarios and imagine various ways to deal with them, while testing the viability of ethical theories that could guide moral judgements and practical decisions made in real life. Buffy the Vampire Slayer (1997-2003) left an important legacy in Popular Culture captivating viewers worldwide and still being relevant 20 years later. The aim of this article is to revisit Buffy’s Season 4 and analyze it through a libertarian perspective. Over this season, a great number of relevant subjects are discussed, such as the form and function of the state, its relationship with society, the subversion of public authorities and the morality of law and punishment. It is expected that the successful adoption of libertarian ethics and principles to understand this TV show might bring out Libertarianism as a valuable philosophical alternative to be taken into account when looking for solutions to current issues.